Schooling the Estate Kids - Parsons, Carl. author. aut Link
XII, 164 p.
Keywords: Schooling the Estate Kids chronicles the trajectory of one Kent secondary school which was twice dubbed ‘the worst school in England’ in the national press. Serving a high poverty neighbourhood, The Ramsgate School was challenged by national targets, low levels of attainment of the school intake at 11 and difficulties of recruitment and retention of quality staff. The local housing estates were amongst the most deprived in the country and shared the school’s negative reputation. The school became The Marlowe Academy in 2005 with new leadership and a new building (in 2006). Student numbers increased, attendance and attainment came close to the national average and the atmosphere in the school was transformed, though the characteristics of the pupils in terms of special needs (twice the national average) and deprivation (more than twice the national average entitled to free school meals) remained unchanged. This book questions the notion that school improvement and school leadership are key areas to focus on when the socio-economic circumstances of pupils, poverty, dwarf all the other factors which are related to the educational progress of students.